Theoretical evaluation of integrated Basin at Risk (iBAR) method for international water conflict-cooperation analysis - Mirhashemi Dehkordi, Seyedeh Simin; Mianabadi, Hojjat; Bagherzadeh, Saeed; Hajiani, Ebrahim; Dehghani Firouzabadi, Seyed Jalal (Frontiers in Water, 2024)
Complex water systems are inherently prone to conflicts, which can have adverse effects on both the environment and human security across various scales. Basin at Risk (BAR) and Integrated Basin at Risk (iBAR) are among recently developed methods to address water conflicts. As an extension of BAR, iBAR emphasizes hidden drivers of water conflict and cooperation, whereas BAR includes visible ones. The novelty of iBAR is grounded in Johan Galtung's theory of violence and the concept of positive peace. This method emphasizes the importance of capturing the hidden aspects of water conflicts as well as the concept of positive peace in water interactions. While iBAR has made significant improvements in addressing water conflicts, some challenges remain. This paper provides a review and theoretical analysis of iBAR. Initially, the iBAR development phases are reviewed in terms of positive peace conceptualization and contextualization in hydropolitical interactions. Following this, the theoretical background of the method is discussed. The results suggest that the iBAR method could be further enhanced by revising concepts of positive peace, social justice, and environmental justice in hydropolitical interactions. By addressing these challenges, water conflicts can be dealt with more effectively.